A Logic Programming Environment for Document Semantics and Inference. - D. Dubin; A. Renear; C.M. Sperberg-McQueen; C. Huitfeldt (Literary & Linguistic Computing, 2003)
Markup licenses inferences about a text. But the information warranting such inferences may not be entirely explicit in the syntax of the markup language used to encode the text. This paper describes a Prolog environment for exploring alternative approaches to representing facts and rules of inference about structured documents. It builds on earlier work proposing an account of how markup licenses inferences, and of what is needed in a specification of the meaning of a markup language. Our system permits an analyst to specify facts and rules of inference about domain entities and properties as well as facts about the markup syntax, and to construct and test alternative approaches to translation between representation layers. The system provides a level of abstraction at which the performative or interpretive meaning of the markup can be explicitly represented in machine-readable and executable form.